2019
DOI: 10.1136/bcr-2018-225929
|View full text |Cite
|
Sign up to set email alerts
|

SAPHO syndrome with enthesopathy

Abstract: Synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome was first described as chronic recurrent multifocal osteomyelitis. Because of its rarity, a thorough description of its clinical manifestations is lacking. Herein, we describe the clinical manifestations and imaging features, especially the enthesopathy in bilateral Achilles tendons, of a middle-aged Asian woman with SAPHO syndrome, who improved after diclofenac treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Fourth, the patients were heterogeneous in terms of disease duration and treatment. Most patients had a complex medical history and treatment process, which may lead to heterogeneous manifestations [15]. Last, future studies should incorporate patient reported outcomes (such as magnitude of pain and upper extremity function) to better understand the clinical relevance of the MRI findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the patients were heterogeneous in terms of disease duration and treatment. Most patients had a complex medical history and treatment process, which may lead to heterogeneous manifestations [15]. Last, future studies should incorporate patient reported outcomes (such as magnitude of pain and upper extremity function) to better understand the clinical relevance of the MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the only method that can detect bone marrow edema (BME) and soft tissue involvement [11]. However, only a few prior reports have specifically investigated the MRI abnormalities of the ACW in SAPHO patients [12][13][14][15]. The aim of our study was to characterize the MRI findings of ACW involvement in SAPHO patients so as to facilitate the understanding of the imaging features and pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are considered to be the first-line drugs for pain relief in patients with SAPHO syndrome. Su et al ( 12 ) reported a 59-year-old female patient who was diagnosed with SAPHO syndrome. Antibiotics used to treat SAPHO were ineffective.…”
Section: Discussionmentioning
confidence: 99%